Using an experiment among clinical experts to determine the cost and clinical impact of rapid whole exome sequencing in acute pediatric settings - Kapol, Nattiya; Kamolvisit, Wuttichart; Kongkiattikul, Lalida; Huang-Ku, Evan; Sribundit, Namfon; Lochid-Amnuay, Surasit; Samprasit, Nathapol; Dulsamphan, Thamonwan; Juntama, Parntip; Suwanpanich, Chotika; Boonsimma, Ponghathai; Shotelersuk, Vorasuk; et al. (Frontiers in Pediatrics, 2023)
Objective Evaluate the cost and clinical impacts of rapid whole-exome sequencing (rWES) for managing pediatric patients with unknown etiologies of critical illnesses through an expert elicitation experiment. Method Physicians in the intervention group (n = 10) could order rWES to complete three real-world case studies, while physicians in the control group (n = 8) could not. Costs and health outcomes between and within groups were compared. Results The cost incurred in the intervention group was consistently higher than the control by 60,000–70,000 THB. Fewer other investigation costs were incurred when rWES could provide a diagnosis. Less cost was incurred when an rWES that could lead to a change in management was ordered earlier. Diagnostic accuracy and the quality of non-pharmaceutical interventions were superior when rWES was available. Conclusion In acute pediatric settings, rWES offered clinical benefits at the average cost of 60,000–70,000 THB. Whether this test is cost-effective warrants further investigations. Several challenges, including cost and ethical concerns for assessing high-cost technology for rare diseases in resource-limited settings, were potentially overcome by our study design using expert elicitation methods.